2020
DOI: 10.1002/celc.201901996
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Glycine with Bimetallic Nickel−Manganese Oxide Catalysts

Abstract: A simple template-free hydrothermal route followed by hightemperature (800°C) annealing in air forms Ni-Mn bimetallic oxides, namely NiMn 2 O 4 , Ni 1.5 Mn 1.5 O 4, and MnNi 2 O 4, which are characterized by XRD, Raman, EDS, and SEM analysis. The electrocatalytic activity of these metal oxides toward the oxidation of glycine molecules in alkaline condition was studied by cyclic voltammetry and linear sweep voltammetry methods. Among other nickel manganese bimetallic oxides and monometallic oxides (Mn 2 O 3 , N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…This phenomenon implies the reversible Ni 2+ /Ni 3+ redox couple during charge/discharge process [53,54] . In Mn 2p 3/2 spectrum of the as prepared sample, as shown in Figure 4B, the deconvoluted peaks at 642.4 and 645 eV can be assigned to Mn 4+ and Mn 4+ satellite peak, respectively [55–57] . The valance of Mn‐ions do not change during first charge process, while partial Mn 4+ have been reduced to Mn 3+ when the cathode discharged to 1.5 V, indicating that more Na + are inserted back into host material due to the deficient reservoir of Na in P2‐Na 0.67 Ni 0.33 Mn 0.67 O 2 phase [58] .…”
Section: Figurementioning
confidence: 90%
See 1 more Smart Citation
“…This phenomenon implies the reversible Ni 2+ /Ni 3+ redox couple during charge/discharge process [53,54] . In Mn 2p 3/2 spectrum of the as prepared sample, as shown in Figure 4B, the deconvoluted peaks at 642.4 and 645 eV can be assigned to Mn 4+ and Mn 4+ satellite peak, respectively [55–57] . The valance of Mn‐ions do not change during first charge process, while partial Mn 4+ have been reduced to Mn 3+ when the cathode discharged to 1.5 V, indicating that more Na + are inserted back into host material due to the deficient reservoir of Na in P2‐Na 0.67 Ni 0.33 Mn 0.67 O 2 phase [58] .…”
Section: Figurementioning
confidence: 90%
“…[53,54] In Mn 2p 3/2 spectrum of the as prepared sample, as shown in Figure 4B, the deconvoluted peaks at 642.4 and 645 eV can be assigned to Mn 4 + and Mn 4 + satellite peak, respectively. [55][56][57] The valance of Mn-ions do not change during first charge process, while partial Mn 4 + have been reduced to Mn 3 + when the cathode discharged to 1.5 V, indicating that more Na + are inserted back into host material due to the deficient reservoir of Na in P2-Na 0.67 Ni 0.33 Mn 0.67 O 2 phase. [58] Therefore, it can be concluded that 0.3 of Na + can deintercalate from P2-NNMO-PMCs cathode per formula unit during first charge process through the oxidation of Ni 2 + to Ni 3 + for charge compensation.…”
mentioning
confidence: 99%
“…Electrolysis of #3 (GlyGl in the anode region of the anion membrane): Fig. 5 shows that NH 4+ –R–COOH is formed when GlyGl is in the anode region, which cannot reach the cathode region through the anion membrane under an electric field, and the amino group in GlyGl is rapidly oxidized and converted at the anode region 27 . Contrast this with Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the formation of ethanol from glycine by HPT processing, it is still hard to clarify the pathway for this transformation because the HPT experiments are conducted under ambient atmosphere and thus the gas phases cannot be analyzed. Conversion of glycine have been widely studied under different conditions such as high pressure 8 , thermal heating 40 , ionizing radiation 41 , protonated condition 42 , high-pressure/temperature water 43 , and electrochemical condition 44 . None of these studies reported the formation of ethanol from glycine, although electrochemical formation of methanol and propanol alcohols was mentioned in a publication 45 .…”
Section: Discussionmentioning
confidence: 99%